GERIBEL Book Assisted by the Book Creator Application for Elementary School Dance Arts Learning - Felin Dyah Nur Arifah; Deasylina da Ary (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
Dance education teacher learning still does not use learning media optimally, learning is less varied and monotonous, and teachers do not master the learning materials. This study aims to create a GERIBEL book learning media assisted by the Book Creator application in dance education subjects. This Research and Development (R&D) study uses the ADDIE development model. Data collection techniques use interviews, observations, questionnaires, tests, and documentation. Data analysis techniques use quantitative descriptive techniques. The study subjects were material expert validators, media expert validators, grade IV teachers and grade IV elementary school students. Material experts have validated the media by obtaining a score of 90% of the "very feasible" criteria and then validated by media experts by obtaining a score of 84% of the criteria "very feasible. The pretest and posttest results were calculated using the normality test, t-test, and N-Gain test. The results of the T-test were 0.000, indicating a Sig (2-tailed) value of less than 0.05, which means that the results of students' pretest and post-test scores differed significantly. Then, for the results of the N-Gain test, a value of 0.4656 was obtained, which is included in the moderate criteria. This study concludes that the GERIBEL book media is very feasible and effective in improving the learning outcomes of dance education on the material of getting to know dance through fable stories in grade IV of elementary school.